Graphene nanoribbon based plasmonic Fresnel zone plate lenses. Issue 27 (15th March 2017) - Deng, Sunan; Butt, Haider; Jiang, Kyle; Dlubak, Bruno; Kidambi, Piran R.; Seneor, Pierre; Xavier, Stephane; Yetisen, Ali K.
Abstract : A graphene-based metamaterial lens is theoretically proposed by combining plasmonic nanoribbons with Fresnel Zone Plate (FZP) architecture to realize wavelength-selective and tunable lensing. Abstract : A graphene-based metamaterial lens is theoretically proposed by combining plasmonic nanoribbons with Fresnel Zone Plate (FZP) architecture to realize wavelength-selective and tunable lensing. The plasmonic FZP lens shows higher focal intensity and efficiency compared to conventional FZP. As compared with normal graphene FZP, the lensing effect of the plasmonic FZP can be enhanced by 83 times. When compared with Au thin film based FZP lenses, the graphene plasmonic lenses can achieve comparable lensing effects, but with a thinner geometry and with an additional advantage of being wavelength selective and tuneable. The analyses of selectivity and tunability of the plasmonic lens show that the plasmonic lens functions as a filter with broadband incident light or as a switch which can be turned on and off via changing the Fermi levels. The diffraction between neighboring graphene nanoribbons and the effect of the substrate on the lensing effect is also discussed. The plasmonic effect of the nanoribbons only contributes to the focal intensity without affecting the diffraction properties of Fresnel zone plate lenses such as focal lengths. This plasmonic FZP lens is an ideal combination of near and far field optics. However, the complex interaction of diffractions within and between the FZP rings could lead to a significant change of the lensing effect, which opens the possibility of creating innovative graphene metamaterial devices. The findings in this work can be used for developing wavelength-selective electro-optical applications operating in the infrared and terahertz ranges.